Cotidal datasets estimation using spatial interpolation methods in Geographical Information System / Khadijah Sahdan - Sahdan, Khadijah (2019)
Some locations along the Malaysian coast do not have any tidal data due to the absence of tide observation. Tide observation stations established by the Royal Malaysian Navy (RMN), International Tidal Survey, and Department of Survey and Mapping Malaysia, along the Malaysian coast are inadequate to gather tidal data at points of interest. Moreover, the existing tide observation stations have limited the usage of tidal data to cover all working areas along the coastal line. Hence, an alternative approach to estimate tidal data, which is a concept of cotidal dataset, has been introduced to provide tidal dataset. This is because gathering cotidal dataset does not require physical tide gauge to be positioned at working areas as well as the need for tide observation for a long period of time. As such, this study presents the estimation of cotidal datasets at selected study areas by employing the spatial interpolation methods and evaluate its output. Interpolation of tidal data from multiple tide observation stations is required in cotidal approach. Hence, three spatial interpolation methods were carried out at two locations along the coast of Peninsular Malaysia as testing grounds. With that, a comparative study of the tidal levels between tidal data acquired from RMN and cotidal dataset through statistical analysis was performed.